What happens next - Hughes, Susan, 1960- (Owlkids Books, 2018)
"Advanced picture book told through first-person narrative and graphic novel style panels. What Happens Next is a raw, realistic story told by an unnamed protagonist who feels different from everybody else, like she doesn't quite fit in. Bullied by a girl at school, our narrator gives a terse script of the related facts and emotions. At school the next day, the narrator confronts the bully by spinning her "weirdo" obsession with science into an opportunity to find common ground, and maybe help the bully see the world in a new way. Spare illustrations in a limited palette of blues and greens convey feeling alone even in the hustle and bustle of a crowded schoolyard."--